Gender differences in educational outcomes and the effect of family background: A comparative perspective from East Asia. (April 2020) - Akabayashi, Hideo; Nozaki, Kayo; Yukawa, Shiho; Li, Wangyang
There is wide variation in the degree of gender gap in test scores around the world, suggesting the strong influence of institutions, culture and inequality. We present comparative evidence on the gender gap in educational achievement in China, Japan, and the USA, with an emphasis on the gender-specific effect of parental income and education, and the child's own preferences for study subjects. We used three major national representative longitudinal surveys with rich information about cognitive outcome measures of respondent children as well as educational investment and parental socio-economic status that allow us to analyze their inter-relationship. We found that low household income tends to have more adverse effects on language test scores for boys than for girls in the USA, as is consistent with previous studies. However, it does not have an impact on gender gap in test scores in China and tends to affect girls more adversely than boys in Japan.